Pengaruh Desain Interior terhadap Kenyamanan Pengguna di Perpustakaan UIN Ar-Raniry Banda Aceh - Muhammad Naufal; Nisa Putri Rachmadani; Mira Alfitri (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Abstract. The college library is a place for students to be used as a science-based recreation area. To fulfill this, a comfort is needed for visitors, especially students, to feel at home and feel / want to continue to linger while in the library. Wicaksana (2016) defines comfort as a relaxed condition, where pain is not felt between all limbs. Factors from the interior of the library also greatly influence students to feel more comfortable when they are in the room in the library. The purpose of this study is to determine the level of user comfort when in the UIN Ar-R aniry library room, especially in the reading area / room which includes lighting, air, and sound efficiency (acoustic) factors. This research uses qualitative methods with descriptive data analysis methods (data coding) and calculations based on the results of questionnaires (Likert scale), observation, and documentation. The results showed that the average visitor was a student of UIN Ar-Raniry and chose to visit in groups, with a frequency of visits ranging from 1 to 3 visits, and a visit time of less than or for 2 hours. Serta prefers to visit during the day (14.00 WIB) to afternoon (16.30 WIB). Common activities are doing assignments or looking for references with the reading room as the most visited area. Based on open questions to respondents and has been categorized, the comfort factor is the reason users want to stay longer in the UIN Ar-Raniry library. Respondent also feels comfortable in terms of lighting and air both naturally and artificially. But for the noise level, occasionally respondents feel a little disturbed due to the sound generated from other users' activities.